Keywords in creative writing - Bishop, Wendy, 1953-2003; Starkey, David, 1962- (UPCC book collections on Project MUSE., 2006)
Keywords in Creative Writing provides a brief but comprehensive introduction to the field of creative writing through its landmark terms, exploring concerns as abstract as postmodernism and identity politics alongside very practical interests of beginning writers, like contests, agents, and royalties. This approach makes the book ideal for the college classroom, and unique in the field, combining the pragmatic accessibility of popular writer's handbooks, with a wider, more scholarly vision of theory and research.